Impact of Traffic in Two Sowing Systems - Draghi, Laura; Jorajuria Collazo, Daniel; Sarena, Daniel; Bailleres, Matías; Melani, Esteban; Castillo, José Manuel; Cerisola, Cecilia; Palancar, Telmo (Agrociencia Uruguay, 2015)
Agricultural farm systems show high levels of mechanization using tractors and machines weighing more than formers. As a consequence, soil compaction is an emerging problem, resulting in the deterioration of the structure of many soils and low yields. The aim of this study was to evaluate the effect of different intensities of traffic on two conditions of soil: low tillage and direct seeding, under different traffic intensities. Two sowing systems were compared: direct seeding and tilled soil sowing. As subtreatments, multiple traffic intensities were applied using one, five and ten passes of a 6.4 Mg tractor. Induced soil compac-tion was assessed by penetration resistance, bulk density and rut depth. In addition the resulting maximum compaction was evaluated using Proctor Test (1933). Tilled soil was more compactable, showing more important rut depths and less penetra-tion resistance after the traffic. The soil under reduced tillage presented lower Proctor compactness and lower optimum moisture. Furthermore, it was found that this soil had a higher percentage of total carbon and particulate carbon, and greater structural stability. The soil under no tillage was able to store more water for a longer period. There was a different rheological behavior under tillage system. The changes in physical properties were more evident in the tilled soil.